Cerebral small vessel disease mediates the association between homocysteine and cognitive function - Teng, Zhenjie; Feng, Jing; Liu, Ronghui; Ji, Yifan; Xu, Jing; Jiang, Xin; Chen, Huifang; Dong, Yanhong; Meng, Nan; Xiao, Yining; Xie, Xiaohua; Lv, Peiyuan (Frontiers in Aging Neuroscience, 2022)
Objective To investigate the relations of serum total homocysteine (tHcy) with cerebral small vessel disease (CSVD) and cognitive function and evaluate whether CSVD mediates the effect of serum tHcy on cognitive function. Methods A total of 1,033 consecutive eligible participants who received serum tHcy, brain magnetic resonance imaging (MRI), and neuropsychological assessment were included in this retrospective study. White matter hyperintensity, lacune, cerebral microbleed, and enlarged perivascular space were evaluated based on brain MRI. We used multivariate binary logistic regression analysis, multivariate ordinal logistic regression analysis, and mediation analyses to assess the relations of serum tHcy with CSVD and cognitive function. Results Serum tHcy levels were higher in patients with cognitive impairment than those with no cognitive impairment. Logistic regression analyses showed elevated serum tHcy was associated with cognitive impairment [odds ratio (OR): 10.475; 95% confidence interval (CI): 4.522 to 24.264; p < 0.001] and a higher CSVD burden score (OR: 17.151; 95% CI: 8.785 to 33.921; p < 0.001) after adjusting potential confounders. Compared with the lowest tHcy quartile, the multivariable-adjusted OR of the highest quartile was 4.851 (95% CI: 3.152 to 7.466; p for the trend < 0.001) for cognitive impairment, 3.862 (95% CI: 2.467 to 6.047; p for the trend < 0.001) for a severe CSVD burden score. Mediation analyses showed significant moderating effects (9.3–23.6%) by different imaging markers of CSVD on the association between higher serum tHcy levels and cognitive impairment. Conclusion Elevated serum tHcy is associated with cognitive impairment and the development of CSVD. A proportion of the association between elevated serum tHcy and cognitive impairment may be attributed to the presence of different imaging markers of CSVD, especially the severe CSVD burden score.